2020
DOI: 10.1111/epi.16661
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of seizure response to vagus nerve stimulation: A scoping review

Abstract: Epilepsy is a serious neurological condition that affects millions of individuals worldwide. 1 Up to 35% of patients do not respond to medications and may benefit from surgical intervention. 2 Although a subset of these individuals are candidates for vagus nerve stimulation (VNS), treatment outcomes following implantation are highly variable. 3 Difficulty in identifying which candidates are likely to benefit from VNS results in some patients incurring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…Neuroimaging methods have further revealed acute and prolonged effects of VNS in thalamic and cortical nodes (15,(24)(25)(26)(27). Recent connectomic studies support these observations by demonstrating that the robustness of leftlateralized microstructure and connectivity within limbic, thalamocortical, and hemispheric association fibers reliably predict VNS therapeutic responsiveness (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 94%
“…Neuroimaging methods have further revealed acute and prolonged effects of VNS in thalamic and cortical nodes (15,(24)(25)(26)(27). Recent connectomic studies support these observations by demonstrating that the robustness of leftlateralized microstructure and connectivity within limbic, thalamocortical, and hemispheric association fibers reliably predict VNS therapeutic responsiveness (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 94%
“…Though our model demonstrated an ability to predict VNS response at a rate slightly better than chance, our analysis demonstrated that clinical variables alone are not sufficient to accurately predict VNS response in this patient population. More advanced data, like biomarkers 16 , are warranted for more accurate predictions of VNS response. This tool may be utilized as an adjunct during the initial outpatient evaluation of seizure control options for pediatric patients with ASM-resistant epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that heart rate variability was an independent marker of VNS response and their results indicated that brain network connectivity analyses are a promising avenue for predicting seizure responsiveness to VNS. 16 Such connectonomic and biomarker analyses have an important role in understanding the mechanism of VNS and could aid patient selection at specialized epilepsy centers. The variables utilized in this study's clinical prediction tool are easily attainable by an outpatient care provider and demonstrates better predictive accuracy (65%) than chance alone.…”
Section: Clinical Predictive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]9,13,14 The vagus nerve has direct afferent projections to the thalamus. 13 Response variation to VNS therapy in children is hypothesized to be attributable to the heterogeneity of seizure etiologies and the age-dependent varying effects of VNS on thalamocortical connectivity of the developing brain, known as the vagus afferent network. 13,15 A better understanding of the characteristics of good and poor responders to VNS therapy in the pediatric population is critical to improve patient selection and response prediction.…”
Section: Introductionmentioning
confidence: 99%